2018
DOI: 10.1177/0954406218790285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity variation on non-Newtonian lubrication of squeeze film conical bearing having porous wall operating with Rabinowitsch fluid model

Abstract: In this study, the effect of viscosity variation of non-Newtonian lubrication on squeeze film characteristics with porous and Rabinowitsch fluid for conical bearings is analyzed. The modified Reynolds equation representing the characteristics of non-Newtonian fluid with viscosity variation on the porous wall followed by the cubic stress law condition is invoked. For lubricant flow in a bearing clearance and in a porous layer Morgan–Cameron approximation is considered. A small perturbation technique is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Some notable studies on the Rabinowitsch fluid model can be found in the literature. 3740 The experimental observation of this fluid model was excellently reported by Wada and Hayashi. 41 To the best of the author's knowledge, no endeavour has been made to attempt this problem for Rabinowitsch fluid in both tube and channel confinements.…”
Section: Introductionsupporting
confidence: 75%
“…Some notable studies on the Rabinowitsch fluid model can be found in the literature. 3740 The experimental observation of this fluid model was excellently reported by Wada and Hayashi. 41 To the best of the author's knowledge, no endeavour has been made to attempt this problem for Rabinowitsch fluid in both tube and channel confinements.…”
Section: Introductionsupporting
confidence: 75%
“…A higher viscosity of the elastic artificial skin compositions could demonstrate stronger resistance against the spread forces applied to the compositions when the artificial skins were synthesized. Therefore, the thickness of the elastic artificial skin was increased when the viscosity of the formulations was increased [ 79 , 80 ]. The difference in thickness of AB0 and of AB15 exhibited a statistical significance of p < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…However, journal bearings with rigid linear and different geometrical configurations and operating conditions are the most studied sliding bearings. We may cite the following study examples: infinitely long, 35 short 36 and finite-length width 37,38 plain and partial bearings, porous bearings, 39 hydrostatic, 40 hybrid, 41 and non-circular elliptical, 42 two-lobe 43 and conical 44 journal bearings, etc. It should be noted that in the literature review, many studies have been reported on elastohydrodynamic lubrication of journal bearings considering the rheological behavior of lubricants.…”
Section: Introductionmentioning
confidence: 99%